Recombinant follitropin alfa/lutropin alfa in fertility treatment - Ahmed Gibreel (Dove Medical Press, 2009)
Ahmed Gibreel1, Siladitya Bhattacharya21School of Medicine and Dentistry, University of Aberdeen; 2Aberdeen Maternity Hospital, Aberdeen, UKAbstract: Recombinant human follicle stimulating hormone (rFSH) and luteinizing hormone (LH), also known as follitropin alpha and lutropin alpha, are manufactured by genetic engineering techniques which ensure high quality and batch to batch consistency. Follitropin alpha can be used for controlled ovarian hyperstimulation in assisted reproduction, ovulation induction for WHO group I and II anovulatory infertility and in men with hypogonadotrophic hypogonadism (HH) or idiopathic oligo-asthenospermia. Current evidence suggests superiority of urinary human menopausal gonadotropin (HMG) over follitropin alpha in controlled ovarian hyperstimulation for IVF in terms of live birth rate per couple. Addition of lutropin to follitropin alpha in an unselected IVF population does not appear to confer any benefit; however, it may have a role in ovulation induction in women with hypothalamic hypogonadism. Urinary HMG preparations (especially currently available highly purified preparations) are more cost effective than rFSH in terms of cost per ongoing pregnancy. However, women using rFSH injection pen devices have higher levels of satisfaction as compared to those using urinary HMG by means of conventional syringes.Keywords: infertility, follicle stimulating hormone, luteinizing hormone, follitropin alpha, lutropin alpha, in-vitro fertilization, urinary gonadotrophins